2005
DOI: 10.1002/qsar.200510102
|View full text |Cite
|
Sign up to set email alerts
|

Use Of The R-Group Descriptor for Alignment-Free QSAR

Abstract: An R-group descriptor characterises the distribution of some atom-based property, such as elemental type or partial atomic charge, at increasing numbers of bonds distant from the point of substitution on a parent ring system. Application of PLS to datasets for which bioactivity data and R-group descriptor information are available is shown to provide an effective way of generating QSAR models with a high level of predictive ability. The resulting models are competitive with the models produced by established Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Based on the results of molecular modeling, an interplay mechanism of BMS small-molecule ligands with PD-L1 was proposed. Finally, R-group based QSAR analysis (Holliday et al, 2003; Hirons et al, 2005) and molecular docking were constructed on the reported BMS small-molecule inhibitors. The results of this study would provide a good guidance for the discovery of novel small-molecule inhibitors and structural modification of BMS small-molecule inhibitors targeting PD-L1.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of molecular modeling, an interplay mechanism of BMS small-molecule ligands with PD-L1 was proposed. Finally, R-group based QSAR analysis (Holliday et al, 2003; Hirons et al, 2005) and molecular docking were constructed on the reported BMS small-molecule inhibitors. The results of this study would provide a good guidance for the discovery of novel small-molecule inhibitors and structural modification of BMS small-molecule inhibitors targeting PD-L1.…”
Section: Introductionmentioning
confidence: 99%
“…It is intuitive that the set of conformers selected should be representative of the entire conformational space; however it is not currently clear as to which method to apply in generating such a set of conformers. Alignment-free descriptor vectors [23,[65][66][67] appear to be the pre-eminent choice for the conformer problem since extant 'diverse' subset selection methods can be applied readily to select conformers that are representative of the entire conformer space and will be effective both within and between individual molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Previously applied to the calculation of inter-substituent similarities, which might be exploited for the identification of bioisosteric groups [16], the R-group descriptor (RGD) was more recently also the subject of QSAR investigations [17]. The RGD describes the distribution of atomic properties at a distance of n bonds (n ¼ 1, 2, 3 y) away from a core that is common to a series of compounds.…”
Section: Molecular Descriptorsmentioning
confidence: 99%